Internal Drivers and Performance Consequences of Small Firm Green Business Strategy: The Moderating Role of External Forces - Leonidou, Leonidas C.; Christodoulides, Paul; Kyrgidou, Lida P.; Palihawadana, Daydanda (My University, 2017)
Growing detrimental effects on the bio-physical environment have been responsible for a large number of small firms to adopt a more strategic stance toward exploiting green-related opportunities. This article aims to shed light on how internal company factors help to formulate a green business strategy among small manufacturing firms, and how this, in turn, influences their competitive advantage and performance. Based on data received from 153 small Cypriot manufacturers, we propose and test a conceptual model anchored on the Resource-based View of the firm. The findings underscore the critical role of both organizational resources and capabilities in pursuing a green business strategy. The adoption of this strategy was more evident in the case of firms operating in more harmful, as opposed to less harmful, industries. The implementation of a green business strategy was found to generate a positional competitive advantage, with this association becoming stronger under conditions of high regulatory intensity, high market dynamism, high public concern, and high competitive intensity. It was also revealed that this competitive advantage is conducive to gaining heightened market and financial performance. Our study makes a fivefold contribution: it injects a theoretical perspective into a relatively atheoretic field, underlines the role of organizational resources/capabilities as drivers of eco-friendly initiatives, highlights the often neglected strategic aspects of small firms’ ecological business activities, stresses the contingent role of external forces in moderating the positive impact of small firm green business strategy on competitive advantage, and focuses on the performance implications of the small firm’s engagement in environmental operations.
Keywords: Resource-based view; Environmental strategy; Business performance; Resources; Capabilities; SMEs